2001
DOI: 10.1063/1.1357795
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of a Langmuir trough experiment carried out on a nanoparticulate array

Abstract: We have used molecular dynamics simulation and thermodynamic arguments to analyze the pressure-area curve resulting from the compression of a monolayer of nanoparticulates at a liquid–vapor interface. The pressure–area isotherm produced by molecular dynamics simulation shows characteristics common to experimental isotherms obtained using the Langmuir-trough technique. The surface pressure exhibits a “knee,” which signals the onset of surface collapse. Visual inspection of the computer simulated monolayers, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Using colloidal particles for studying monolayer films in an LB trough also triggered interest in computer modeling of the processes during the films compression. Tolnai et al and Fenwick et al presented a computer simulation of the compression process and Agod et al investigated the effect of particle polydispersity onto the compression process, making realistic assumptions of the particle size distribution (up to 7–8% polydispersity range) 24–26. Some of the theoretical predictions (particle “buckling” during the compression) have been observed experimentally.…”
Section: Monolayer Deposition Of Colloidal Sio2 Spheresmentioning
confidence: 99%
“…Using colloidal particles for studying monolayer films in an LB trough also triggered interest in computer modeling of the processes during the films compression. Tolnai et al and Fenwick et al presented a computer simulation of the compression process and Agod et al investigated the effect of particle polydispersity onto the compression process, making realistic assumptions of the particle size distribution (up to 7–8% polydispersity range) 24–26. Some of the theoretical predictions (particle “buckling” during the compression) have been observed experimentally.…”
Section: Monolayer Deposition Of Colloidal Sio2 Spheresmentioning
confidence: 99%
“…In particular, a molecular dynamics approach was adopted separately by Ferwick et al. [4] and Nielsen et al [5] for this purpose. However, this type of simulation requires individual solvent molecules to be simulated explicitly, which is rather expensive in computational terms.…”
Section: Introductionmentioning
confidence: 99%
“…play a useful role by studying the effect of one factor at a time to help elucidate experimental observations and uncover new physical insights. [19][20][21][22][23][24][25][26][27] For example, Bresme and Quirke showed that Young's equation can be used to describe force balance at nanoscale interfaces, but in certain cases line tension should also be included. 19 Fenwick and Powell et al showed that contrary to expectations, the collapse pressure measured in a typical Langmuir trough experiment should be independent of the contact angle.…”
Section: Introductionmentioning
confidence: 99%
“…19 Fenwick and Powell et al showed that contrary to expectations, the collapse pressure measured in a typical Langmuir trough experiment should be independent of the contact angle. 20,21 Recently, Cheung showed the importance of nanoparticle-liquid interactions and capillary waves in determining the stability of nanoparticles at liquid interfaces. 25 Although MD simulations to date have revealed many important aspects of the physical behavior of nanoparticles at an interface, some aspects are still unclear.…”
Section: Introductionmentioning
confidence: 99%